Peripheral cutaneous synucleinopathy characteristics in genetic Parkinson’s disease - Yuan, Yanpeng; Wang, Yangyang; Liu, Minglei; Luo, Haiyang; Liu, Xiaojing; Li, Lanjun; Mao, Chengyuan; Yang, Ting; Li, Shuo; Zhang, Xiaoyun; Gao, Yuan; Xu, Yuming; et al. (Frontiers in Neurology, 2024)
Background Cutaneous phosphorylated alpha-synuclein (p-α-syn) deposition is an important biomarker of idiopathic Parkinson’s disease (iPD). Recent studies have reported synucleinopathies in patients with common genetic forms of PD. Objective This study aimed to detect p-α-syn deposition characteristic in rare genetic PD patients with CHCHD2 or RAB39B mutations. Moreover, this study also aimed to describe peripheral alpha-synuclein prion-like activity in genetic PD patients, and acquire whether the cutaneous synucleinopathy characteristics of genetic PD are consistent with central neuropathologies. Methods We performed four skin biopsy samples from the distal leg (DL) and proximal neck (C7) of 161 participants, including four patients with CHCHD2 mutations, two patients with RAB39B mutations, 16 patients with PRKN mutations, 14 patients with LRRK2 mutations, five patients with GBA mutations, 100 iPD patients, and 20 healthy controls. We detected cutaneous synucleinopathies using immunofluorescence staining and a seeding amplification assay (SAA). A systematic literature review was also conducted, involving 64 skin biopsies and 205 autopsies of genetic PD patients with synucleinopathy. Results P-α-syn was deposited in the peripheral cutaneous nerves of PD patients with CHCHD2, LRRK2, or GBA mutations but not in those with RAB39B or PRKN mutations. There were no significant differences in the location or rate of α-syn-positive deposits between genetic PD and iPD patients. Peripheral cutaneous synucleinopathy appears to well represent brain synucleinopathy of genetic PD, especially autosomal dominant PD (AD-PD). Cutaneous α-synuclein SAA analysis of iPD and LRRK2 and GBA mutation patients revealed prion-like activity. Conclusion P-α-syn deposition in peripheral cutaneous nerves, detected using SAA and immunofluorescence staining, may serve as an accurate biomarker for genetic PD and iPD in the future.